Hypocotyl Elongation Inhibition of Melatonin Is Involved in Repressing Brassinosteroid Biosynthesis in Arabidopsis - Xiong, Fangjie; Zhuo, Fengping; Reiter, Russel J.; Wang, Lingling; Wei, Zhenzhen; Deng, Kexuan; Song, Yun; Qanmber, Ghulam; Feng, Li; Yang, Zuoren; Li, Fuguang; Ren, Maozhi (Frontiers in Plant Science, 2019)
Melatonin functions as a plant hormone/regulator in the regulation of growth and development. However, the underlying mechanisms are still unclear. In this study, we found high dose of melatonin inhibited hypocotyl elongation in a dose-dependent manner in Arabidopsis. Expression profile analysis showed that hypocotyl growth inhibition by melatonin was involved in reprograming the expression of cell elongation genes and brassinosteroids (BRs) biosynthetic genes. Furthermore, similar to BR biosynthetic inhibitor brassinazole (BRZ), high concentration of melatonin upregulated BR-biosynthetic genes and downregulated BR-induced genes involved in cell elongation, while melatonin was inefficient to brassinazole-resistant mutants like the bzr1-1D and bes1-D in hypocotyl inhibition. Comparative expression profile analysis showed opposite expression mode between melatonin-induced and bzr1-1D or brassinolide (BL)-induced in their co-regulated genes. Additionally, exogenous BL rescued the repressive phenotype of BR biosynthesis deficient mutant like det2-1 even in presence of high dose melatonin, but not BR receptor mutant bri1-5 or signal transduction mutant bin2-1. Biochemical analysis furtherly confirmed melatonin reduced endogenous BRs levels in a dose-dependent manner in Arabidopsis. Taken together, these results indicate that melatonin inhibits BRs biosynthesis but does not block BR signaling in inhibition of hypocotyl elongation, and extends insights the role of melatonin in cross-talking with plant hormones signaling.